IL-4, IL-10, TNF-α and IFN-γ Cytokine Levels in Patients with Cystic Echinococcosis and Fascioliasis - Yunus Emre Beyhan; Cuneyt Albayrak; Irem Guven (Tehran University of Medical Sciences, 2022)
Background: Cytokines are protein substances involved in immune response and inflammation regulation, cell growth, tissue repair and natural and adaptive immunity events such as hematopoiesis. Changes in Th1 and Th2 immune responses provide information on the clinical presentation, pathology and diagnosis of diseases. Methods: This study was conducted on 142 patients, aged 18-95 yr and applied to Parasitology Laboratory of Van Yuzuncu Yil Hospital between Aug 2018 and May 2019. Fifty-one of the patients were serologically diagnosed with CE, 53 with a diagnosis of fascioliasis, and 38 as the control group. Serum samples were taken from patients and levels of IL-4, IL-10, TNF α and IFN γ parameters were investigated by ELISA method. Results were evaluated by spectrophotometer and observed which immunologic parameters increased in which infections. Cytokine results were also evaluated according to patient age groups and genders. Chi-square and/or Fisher's exact test were used to evaluate the results. IL-4 response was detected in 50.9%; IL-10 in 44.2%; TNF-α in 43.3% and IFN-γ in 43.3% of CE seropositive patients. Results: IL-4, IL-10, TNF-α and IFN-responses detected in 50.9%, 44.2%, 43.3% and 43.3% of CE patients, and in 43%, 39.2%, 34.4% and 40.6% of fascioliasis patients, respectively. The presence of Th1 and Th2 responses were detected in both infections. There was a significant relationship between fascioliasis and IL-4 response and between CE and IL-4, IL-10 and TNF-α responses (P≤.05). Conclusion: These cytokine levels may provide information about the immune response to infections, and may be useful for early detection of disease and recurrence and monitoring of treatment.